Epidemiological shift of hepatitis A in central Adana, Turkey - Alhan, Emre; Kozanoğlu, Banu; Tümgör, Gökhan; Çelik, Ümit; Yaman, Akgün; Bozdemir, Nafiz (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The aim of the study was to determine the epidemiological shift that may have occurred in the last 11 years of Hepatitis A virus (HAV) seroprevalence. Materials and Methods: In 1998, we reported the anti-HAV seroprevalence in 711 children aged between 2 and 16 years children in Adana city center. Eleven years later we repeated the same study at the same locations in a similar population with the same method. Results: From 1998 to 2009 anti-HAV seroprevalence declined from 33.9 % to 22.2 %, 29.5 % to 25.3 % (p>0,05), 52.2 % to 30.8 %, 69.7 % to 35.2 %, 66.9 % to 37.7 % and 71.4 % to 47.3 % (p<0,0001) in the age groups of 48-71, 72-95, 96-119, 120-143, 144-167 and 168-198 months respectively. Conclusion: Our study showed that anti-HAV seroprevalence has decreased statistically significantly during the last 11 years in school-aged children. Results showed that anti-HAV seroprevalence has shifted to further ages. Since adolescents and young adults are at risk of symptomatic HAV infection, routine hepatitis A vaccination of children will be initiated in 2012 in Turkey.